2013
DOI: 10.1051/0004-6361/201220783
|View full text |Cite
|
Sign up to set email alerts
|

Deep, wide-field, global VLBI observations of theHubbledeep field north (HDF-N) and flanking fields (HFF)

Abstract: Context. Dust is commonly present in weakly radio emitting star-forming galaxies and this dust may obscure the signatures of accreting black holes in these objects. Aims. We aim to uncover weak active galactic nuclei, AGN, in the faint radio source population by means of deep high-resolution radio observations. Methods. VLBI observations with a world-wide array at unparallelled sensitivity are carried out to assess the nature of the faint radio source population in the Hubble deep field north and its flanking … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
78
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(97 citation statements)
references
References 54 publications
15
78
4
Order By: Relevance
“…Although limited in a statistical sense, our findings are supported by similar results by Herrera Ruiz et al (2016), who found VLBI cores in RQ QSOs in the COSMOS field. Further support comes from the 12 RQQ sources (according to the classification of Bonzini et al 2013) observed by Chi et al (2013), four of which were detected with VLBI.…”
Section: Discussionmentioning
confidence: 95%
“…Although limited in a statistical sense, our findings are supported by similar results by Herrera Ruiz et al (2016), who found VLBI cores in RQ QSOs in the COSMOS field. Further support comes from the 12 RQQ sources (according to the classification of Bonzini et al 2013) observed by Chi et al (2013), four of which were detected with VLBI.…”
Section: Discussionmentioning
confidence: 95%
“…Ten of them were previously detected with VLBI at 1.4 GHz by Chi et al (2013). VLBI cores are found to account for, on average, 30 percent of the total 1.6 GHz emission.…”
Section: 4 Ghz Vlbi Detectionsmentioning
confidence: 94%
“…We show the radio sources for which the submillimeter flux measurement at the radio position has a signal-to-noise ratio (S/N) ≥ 2 σ as circles with 1 σ uncertainties, and we show S/N< 2 σ as circles at the 2 σ limit with downward pointing arrows. We use colors to denote the sources classified as either compact (Chi et al 2013;cyan) or extended (Momjian et al 2010; red) from VLBI data. Finally, we denote with green shading the factor of two range found by Barger et al (2014) over which we expect the SFRs derived from the submillimeter fluxes to be consistent with the SFRs derived from the radio power, assuming the FIR-radio correlation with the radio emission dominantly powered by star formation.…”
Section: Vlbimentioning
confidence: 99%